Understanding the mechanism of land-cover related climate change in the low latitudes - PAETH, HEIKO (MAUSAM, 2008)
Rainfall variability in the low latitudes in general and over tropical and sub-tropical Africa in particular, is largely affected by land surface characteristics like, vegetation cover, albedo and soil moisture. Understanding the local and dynamical effects of land-cover changes is crucial to future climate prediction, given ongoing population growth and increasing agricultural needs in Africa. Here, a set of sensitivity studies with a synoptic-scale regional climate model is presented, prescribing idealized scenarios of reduced vegetation cover over Africa. Beside the vegetation ratio itself, the leaf area index, forest ratio, surface albedo and roughness length are changed as well, in order to obtain a consistent scenario of land surface degradation. In addition, a second set of experiments is realized with altered soil parameters as expected to be coming alongwith a reduction in vegetation cover. Seasonal rainfall amount decreases substantially when the present-day vegetation continuously disappears. The strongest changes are found over the Congo Basin and subsaharan West Africa, where the summer monsoon precipitation diminishes by up to 2000 mm and 600 mm, respectively. The rainfall response to vegetation changes is non-linear and statistically significant over large parts of subsaharan Africa. Convective precipitation is more sensitive than large-scale precipitation. The most prominent effect of land degradation is a decrease (increase) of latent (sensible) heat fluxes. As a consequence, the large-scale thermal gradients, as a key factor in the monsoonal flow over Africa, are modified leading to a southward shift of the intertropical convergence zone and enhanced moisture advection over the southernmost part of West Africa and the central Congo Basin. The mid-tropospheric jet and wave dynamics are barely affected by land-cover changes. Although the large-scale dynamical response is favourable to increasing rainfall amount, the moisture budget is predominantly governed by reduced evapotranspiration, overcompensating the positive dynamical effect and inducing a weakening of the regional-scale water recycling. The related changes in the soil properties may additionally contribute to a reduction in rainfall amount, albeit of lower amplitude.